Strut and tie modeling for RC short beams with corroded stirrups - Ahmed K. El-Sayed (Latin American Journal of Solids and Structures)
Corrosion of steel reinforcement is one of the major problems that shorten the service life of reinforced concrete (RC) structures. Steel stirrups, due to their location as an outer reinforcement, are more susceptible to corrosion problems and damage. However, there is limited research work in the literature on the effects of stirrup corrosion on the shear strength of RC beams. This paper attempts to evaluate analytically the residual shear strength of RC short beams with corrosion-damaged stirrups. The shear strength of short or deep beams are generally determined using the strut and tie model. The corrosion effects were implemented in the model to make it capable of predicting the residual shear capacity of RC beams with corroded stirrups. The effect of corrosion is implemented considering the reduction in geometry of the concrete cross section due to spalling and reduction in effective compressive strength of concrete due to corrosion cracks. The proposed strut and tie model which accounts for the corrosion effects was verified using the experimental data available in the literature, and good agreement was found.